Studying 630 nm atomic oxygen emission sources during strong magnetic storms in the night mid-latitude ionosphere - Leonovich L.A.; Tashchilin A.V.; Lunyushkin S.B.; Karavaev Yu.A.; Penskikh Yu.V. (Solar-Terrestrial Physics, 2019)
We analyze significant increases in 630 nm atomic oxygen night emissions during very strong geomagnetic storms, using optical measurements, theoretical modeling, and magnetogram inversion technique (MIT) data. It is shown that during strong magnetic storms when electron precipitation equatorial boundary at the night sector expands up to ~40°, the interaction of energetic electron flux with thermospheric components may cause extreme increases in the 630 nm emission intensity. Model calculations of the red line intensity show good agreement with observational data. Using the November 20, 2003 magnetic storm as an example, we have found that oxygen atom collisions with thermal Maxwell and superthermal electrons make a major contribution to the integral emission intensity. Thermospheric density variations during the magnetic storm significantly affect the red line generation.